THE USE OF ‘GRAMMARLY’ APPLICATION AS ELECTRONIC FEEDBACK ON STUDENTS’ WRITING OF ENGLISH THESIS AT UNIVERSITIES IN TERNATE CITY - Sutaryo Sutaryo; Asrul Asrul; Nurprihatina Hasan (Jurnal Bilingual, 2021)
The development of technology and learning English is towards the concept of providing electronic feedback. This research aims: 1). To find out electronic feedback with ‘Grammarly’ in students' writing of English thesis, and 2). To find out the lecturers’ perceptions and experiences related to the use of the 'Grammarly' application as electronic feedback, including in students’ writing of English thesis at universities in Ternate City. Ten lecturers as supervisors and five research proposal texts of thesis from the three universities in Ternate (Khairun University, Muhammadiyah University of North Maluku, and the Teaching and Education College (STKIP)) became the sources of the data in this study. Data collection techniques in this study were carried out using documents and interviews. The collected data were analyzed using thematic analysis (thematic analysis). The findings show that the use of the 'Grammarly' application in the text of the student thesis research proposal revealed some feedback on the errors in students’ writing of their thesis research proposal. Feedback on errors that occur in all existing texts is primarily related to spelling, followed by grammar (grammar) such as the use of articles (article), plural markers, prepositions, and subject-verb agreement. In addition, errors that occur in some thesis proposal texts are the use of punctuation and capital letters. Ten lecturers’ interview data show a positive perception in the use of 'Grammarly'. However, only four have used its application and six other lecturers have not used it.